A taste of home - James, Anna (Romance author) (James, Anna (Romance author). Sisterhood of chocolate & wine., 2023)
Chef Layla Williams enjoys culinary success at her family's coastal Massachusetts bistro, but finds she needs EMT Shane Kavanaugh's help in cementing her legacy.